FACTORS AFFECT FINANCIAL DISTRESS IN CONVENTIONAL BANKING LISTED ON THE INDONESIAN STOCK EXCHANGE - Muchtar, Susy; Sari, Wahyuni Rusliyana; Elgi, Afrizal; Martinistiyas, Catur Rahayu; Elgammal, Mohammed (Universitas Muria Kudus, 2025)
COVID-19 and the Russian-Ukrainian conflict caused global inflationary pressure. This condition enables banks worldwide to implement a policy of increasing interest rates, which can lead to high inflation. High inflation can cause financial distress in various sectors, including banking, which is a crucial sector in the economy. This research aims to identify the factors that contribute to financial distress. The sample used in the study consisted of 35 conventional banks listed on the Indonesia Stock Exchange from 2018 to 2022, and a logistic regression analysis was employed. The results of discriminant analysis in this study indicate that banks with a high solvency ratio may face a higher probability of financial distress. In contrast, higher profitability ratios decrease the risk of financial distress. Our results can encourage regulators and policymakers to adopt policies that maintain capital adequacy and increase banking profits, thereby avoiding financial distress, especially during economic downturns. It is hoped that the results of this research will serve as a reference for conventional banks to prevent financial distress by optimizing capital management and enhancing bank profitability.